Concept mapping and conceptual change texts: a constructivist approach to address the misconceptions in nanoscale science and technology - Naeem Sarwar, Muhammad; Shahzad, Asif; Ullah, Zaka; Raza, Shahid; Wasti, Shahbaz Hassan; Shrahili, Mansour; Elbatal, Ibrahim; Kulsoom, Sumaira; Qaisar, Shahzada; Faizan Nazar, Muhammad (Frontiers in Education, 2024)
Nanoscale Science and Technology (NST) is a rapidly evolving field with profound implications for various industries and our everyday lives. However, misconceptions among learners can hinder their ability to grasp the fundamental concepts of NST, thereby impeding their potential contributions to this advancing domain. Concept maps (CM) and conceptual change texts (CCT) are graphical and written representations of knowledge that enable learners to visualize relationships between concepts and assess the coherence of their understanding. In this pursuit, we engage with the concept of rehabilitation for misconceptions, viewing the learning process as a transformative journey akin to cognitive rehabilitation. Through this CM-CCT constructivist approach, learners are encouraged to engage in critical reflection, self-questioning, and peer discussions, which facilitate the identification of misconceptions. Moreover, CM-CCT provide a structured framework for presenting accurate information about NST, offering a clear depiction of the hierarchical and interconnected nature of nanoscale phenomena. The aim of this study was to evaluate the effectiveness of CM-CCT in correcting the misconceptions of undergraduate university students regarding nanotechnology and the taxonomy of nonmaterial. Prior to the implementation of the CM-CCT, an assessment of pre-existing knowledge of the students was performed through the structure of the observed learning outcomes (SOLO) taxonomy. A quasi-experimental research design was carried out. A total of 70 undergraduate university students, divided into two intact groups, were cross-examined for the study. Further, before and after the instructional tools, an achievement test based on nanotechnology and classification of nonmaterial was conducted, covering all six cognitive domains of the Bloom taxonomy of educational objectives. Data analysis revealed that the instructional tools based on constructivist approach had a statistically significant impact on students for elimination of their misconceptions about nanotechnology, nano science and classification of nonmaterial.